Informal micro, small, and medium-sized enterprises and digitalization: Evidence from surveys in Indonesia - Shigehiro Shinozaki (Asian Development Bank Institute (ADBI), 2022)
Most micro, small, and medium-sized enterprises (MSMEs) operate informally. While informal sectors are thought to contribute less to national economic development, MSMEs are a driving force behind national economic growth. Thus, formalizing informal MSMEs is critical to boosting national productivity, creating quality jobs, and promoting inclusive growth. This paper examines the coronavirus disease (COVID-19) impact on informal MSMEs in Indonesia by using a linear probability model regression and descriptive analysis based on evidence obtained through year-long surveys from March 2020 to May 2021. It also assessed the extent of the digital transformation and challenges brought on by the pandemic and derives policy implications. The estimates found two streams of business clusters among informal MSMEs-contracting firm groups that suffered through the pandemic and those that benefitted. The COVID-19 crisis and mobility restrictions led many informal MSMEs to accelerate digitalization. But digitally operated firms could not always operate successfully during the pandemic, splitting businesses into those profitable or less profitable.
Keywords: D22; G20; L20; L50; 330; COVID-19; informality; shadow economy; MSMEs; digitalization; SME development; access to finance; SME policy; Indonesia